Developing an eco-cultural educational centre at IIUM Gombak campus - Din, Nur Aisyah; Abu Bakar, Aniza; Othman, Jamilah (Kulliyyah of Architecture and Environmental Design, IIUM, 2023)
Environmental and cultural education are vital and have historically aided official and informal education. It will be a great experience for the learners to apply their knowledge in a real-world context. However, it is possible that it will not be integrated into official teaching in higher learning institutions. It can be seen from the way the campus grounds are designed. An initiative that can be done to deliver high-quality education on environmental and cultural awareness is to create spaces for focused education or edu-tourism attractions. Hence, this project intends to create a proposal to develop an eco-cultural educational centre on the IIUM Gombak campus. It will be designed through environmental preservation to create nature-based experiential learning outdoor spaces. The strategies would be to identify environmental education categories and experiential learning principles for incorporating them into landscape design, analyse the site's natural and cultural resources to identify opportunities, and formulate relevant landscape design strategies for eco-cultural education using an experiential learning approach. The study used a combination of descriptive and numerical analysis to identify natural and cultural resources as well as the potential of the area. According to the study, the IIUM campus grounds, with their natural resources and cultural settings, offer significant potential for development as an eco-cultural educational institution. Thus, a landscape master plan for an eco-cultural educational centre on the IIUM Gombak campus, as well as a detailed development plan focusing on the Rumah Kutai area, have been put forth.